Prospective analysis of the management of small bowel obstruction using oral contrast agent at tertiary care hospital in western Rajasthan - Kumar, Ashok; Prasad, Rajendra; Jakhar, Diwan Singh; Jajra, Dharmveer; Chhabra, Sanjeev Kumar; Rai, Ashish (International Surgery Journal, 2018)
Background: Intestinal obstruction is a frequently seen entity in the Emergency Department that represents 25% of abdominal pain consultations. Methods: This prospective, randomized, and clinical trial study was designed to determine the value of gastrografin in adhesive small bowel obstruction. The primary end points were the evaluation of the operative rate reduction and shortening the hospital stay after the use of gastrografin. A total of 100 patients were randomized into two groups: the control group received conventional treatment, whereas the study group received in addition of 100 ml gastrografin meal. Patients were followed up within 4 days after admission, and clinical and radiological (if needed) improvements were evaluated. Results: Surgical procedure was performed in 10% of the gastrografin group for whom conservative treatment failed at the end of fourth day. In contrast, surgery was required in 28% of control group. These findings shows that gastrografin decreased the need for surgical management by 18%, but no statistically significant differences were observed. The length of hospital stay revealed a significant reduction from 4.60±1.14 days to 2.64±1.05 days for control and gastrografin groups, respectively. Conclusions: The use of gastrografin in adhesive small bowel obstruction is safe and reduces the length of hospital stay.